Syntax Interference on Translation of Indonesia-English Text - Dian Nashrul Munif; Budi Setiawan (International Journal of English Learning and Applied Linguistics (IJELAL), 2020)
This study aims to describe the type of syntactic interference in the translation of Indonesian text into English, where students are given a text containing 300 words to be translated into English. The method used in this research is descriptive with distributional and equivalent studies. The data is taken from the translation of the text which is then analyzed for errors. The results showed that there was a syntactic problem that emerged from the translation results of students. Some of the syntactic interference that was found included reversed English phrase arrangement, parallelization, absence of articles, absence of to be, and lack of passive sentence structure.